2021
DOI: 10.3390/molecules26092630
|View full text |Cite
|
Sign up to set email alerts
|

Oxyresveratrol Ameliorates Dextran Sulfate Sodium-Induced Colitis in Rats by Suppressing Inflammation

Abstract: Colitis causes destruction of the intestinal mucus layer and increases intestinal inflammation. The use of antioxidants and anti-inflammatory agents derived from natural sources has been recently highlighted as a new approach for the treatment of colitis. Oxyresveratrol (OXY) is an antioxidant known to have various beneficial effects on human health, such as anti-inflammatory, antibacterial activity, and antiviral activity. The aim of this study was to investigate the therapeutic effect of OXY in rats with dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The extract suppressed inflammation and stimulated mucin production in a manner similar to that of ORV [ 171 ]. In a rat model of dextran sulfate sodium (DSS)-induced colitis, ORV reduced inflammation within the intestine by inhibiting COX-2, iNOS expression, and apoptosis of the epithelial cells [ 184 ]. Another investigation using a mouse model of ethanol-induced ulcer found that pretreatment with oral ORV reduced ulcer scores and ulcer index, as determined from the increased gastric pH and the decreased expression levels of IL-6, TNF-α, NF-ĸB, and COX-2, with unaltered COX-1 expression levels [ 183 ].…”
Section: Biological and Pharmacological Activitiesmentioning
confidence: 99%
“…The extract suppressed inflammation and stimulated mucin production in a manner similar to that of ORV [ 171 ]. In a rat model of dextran sulfate sodium (DSS)-induced colitis, ORV reduced inflammation within the intestine by inhibiting COX-2, iNOS expression, and apoptosis of the epithelial cells [ 184 ]. Another investigation using a mouse model of ethanol-induced ulcer found that pretreatment with oral ORV reduced ulcer scores and ulcer index, as determined from the increased gastric pH and the decreased expression levels of IL-6, TNF-α, NF-ĸB, and COX-2, with unaltered COX-1 expression levels [ 183 ].…”
Section: Biological and Pharmacological Activitiesmentioning
confidence: 99%
“…Supplementation with OXY inhibited activation of MAPK cascades and suppressed secretion of pro-inflammatory mediators from RAW 264.7 following exposure to an inflammatory stimulus in the form of lipopolysaccharide (LPS) [6][7][8][9]. Similar protective results were observed from many preclinical models of inflammation-related diseases, e.g., spinal cord injury [10], neurodegenerative disorder [11], gastric ulcer [12], and colitis [13]. Although OXY has excellent anti-inflammatory effects, the major obstacles to the pharmaceutical use of this polyphenolic stilbene are mainly due to its physicochemical and pharmacokinetic properties.…”
Section: Introductionmentioning
confidence: 59%
“…All column chromatography was performed using silica gel 60 (70-230 mesh) purchased from Merck Millipore (Darmstadt, Germany). 1 H-and 13 C-NMR spectra were recorded on a Bruker NMR spectrometer operating at 300 MHz for 1 H and 75 MHz for 13 C (Bruker Company, Fällanden, Switzerland). Mass spectra were measured by high-resolution electrospray ionization mass spectra (HR-ESI-MS) (Bruker Company, Billerica, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In a Caco-2 model, oxyresveratrol treatment markedly reduced monolayer permeability by upregulating the gene and protein expression of ZO-1, Claudin-1, and Occludin, which are involved in protein kinase C (PKC) and mitogen-activated protein kinase (MAPK) pathways [ 44 ]. Oxyresveratrol has also been reported to alleviate colitis in rats by inhibiting intestinal inflammation [ 45 ]. Oxyresveratrol treatment significantly downregulated the gene expression of pro-inflammatory factors (IL-6, IL-1β, and TNF-α), but upregulated the gene expression of anti-inflammatory factors (IL-10).…”
Section: Plant-derived Polyphenol Application To Counteract Oxidative...mentioning
confidence: 99%
“…Oxyresveratrol treatment significantly downregulated the gene expression of pro-inflammatory factors (IL-6, IL-1β, and TNF-α), but upregulated the gene expression of anti-inflammatory factors (IL-10). Moreover, the expression of COX-2 and iNOS was inhibited by oxyresveratrol supplementation [ 45 ]. Similarly, Ramulus mori ethanol extract, enriched in oxyresveratrol, alleviated acute colitis by inhibiting intestinal inflammation and promoting mucin production in a mouse model as well as in a LS 174T goblet cell line model [ 46 ].…”
Section: Plant-derived Polyphenol Application To Counteract Oxidative...mentioning
confidence: 99%